SOSIALISASI EPILEPSI DAN PELATIHAN PENANGANAN AWAL KEJANG PADA KADER PUSKESMAS CAKRANEGARA - Setiarini, Rohmania; Dian Rahadianti; Nadira Yumna; Herlinawati (P3M Universitas Aisyiyah Surakarta, 2024)
Background: Epilepsy is a brain disorder characterized by a persistent tendency to produce epileptic seizures with neurobiological, cognitive, psychological and social consequences. About 70% of people with epilepsy should be seizure free if properly diagnosed and treated. The risk of death in people with epilepsy is three times higher than in the general population. In Indonesia, the stigma about epilepsy is quite high, there are many wrong assumptions and views about epilepsy. Target and output: The target is the cadres at the Cakranegara Health Center, Mataram, West Nusa Tenggara. The output of this activity is to increase knowledge about epilepsy so that it can eliminate the stigma of epilepsy in society. In addition, increasing knowledge about the initial management of seizures. Method: The method is carried out using several media, namely the presentation of material by neurologists, video, posters and discussions. The increase in participants' knowledge was assessed by completing tests, which were carried out before and after the presentation of the material, video dan posters. Result and conclusion: Based on the data obtained, the implementation of this activity has been successful. This can be seen from the post-test scores which increased by 64%.